Input-dependent synaptic suppression by pregabalin in the central amygdala in male mice with inflammatory pain - Sumii Yamamoto (Elsevier, 2021)
Pregabalin (PGB) is a synthetic amino acid compound most widely prescribed for chronic peripheral and central neuropathic pain. PGB is a ligand for the α2δ1 subunit of voltage-dependent calcium channels, and its binding reduces neurotransmitter release and thus inhibits synaptic transmission. The central nucleus of the amygdala (CeA) is a kernel site for the enhanced nociception-emotion link in chronic pain. The nociceptive information is conveyed to the CeA via the following two pathways: 1) the pathway arising from the basolateral amygdala (BLA), which carries nociceptive information mediated by the thalamocortical system, and 2) that arising from the external part of the pontine lateral parabrachial nucleus (LPB), that forms the final route of the spino-parabrachio-amygdaloid pathway that conveys nociceptive information directly from the superficial layer of the spinal dorsal horn. We compared the effects of PGB on the excitatory postsynaptic currents of neurons in the right CeA in response to electrical stimulation of BLA and LPB pathways using the whole-cell patch-clamp technique. Inflammatory pain was induced by intraplantar injection of formalin solution at the left hind paw.At eight hours post-formalin, PGB reduced EPSCs amplitude of the BLA-to-CeA synaptic transmission, accompanied by a significant increase in the PPR, suggesting a decreased release probability from the presynaptic terminals. In addition, these effects of PGB were only seen in inflammatory conditions. PGB did not affect the synaptic transmission at the LPB-to-CeA pathway, even in formalin-treated mice. These results suggest PGB improves not simply the aberrantly enhanced nociception but also various pain-associated cognitive and affective consequences in patients with chronic nociplastic pain.